Pre-adopting new urban areas to climate change with coastal Nature-based solutions - Haoqi Wang; Baolong Han; Tong Wu; Felix Leung; Yingqi Ren (Ecological Indicators, 2025)
Global climate change-induced phenomena such as sea-level rise and coastal hazards increasingly threaten coastal communities. As a proactive strategy, integrating Nature-based Solutions (NbS) into urban planning is critical for enhancing climate resilience, yet existing frameworks lack spatial and ecosystem-based assessments tailored for new cities. This study develops a Comprehensive Coastal Vulnerability Index (CCVI) that integrates risk and resilience metrics and proposes an innovative spatial decay model to quantify inland vulnerability propagation under sea-level rise. Using Hong Kong’s planned Northern Metropolis Development (NMD) as a case study, we simulate vulnerability dynamics under the 2100 sea-level rise scenario (SSP4.5), urbanization scenario, and NbS habitat restoration scenario. Results reveal that sea-level rise increases coastal vulnerability by 20.73% compared to the 2021 baseline, while NbS habitat restoration reduces vulnerability by 6.01%. Notably, combining NbS with urbanization achieves a 7.52% reduction, demonstrating the efficacy of preemptive spatial planning. Spatial analysis identifies high-risk clusters in eastern NMD (e.g., Sha Tau Kok Bay), where natural habitat coverage is minimal. The CCVI framework advances coastal vulnerability assessments by embedding resilience metrics and spatial heterogeneity, offering actionable insights for policymakers to prioritize NbS in new city masterplans. This study underscores the imperative of coupling ecological restoration with infrastructure to achieve sustainable coastal development in rapidly urbanizing regions.